Indikator Keberhasilan dalam Evaluasi Program Pendidikan: Success Indicators in Educational Program Evaluation - Zahroh, Fitri Lutfia; Hilmiyati, Fitri (ITScience (Information Technology and Science), 2024)
The importance of educational program evaluation lies in its function as a tool to assess the effectiveness and impact of the program being implemented. Evaluation covers not only academic aspects but also social, psychological, and life skills aspects of students. Success indicators are the key to the evaluation process because they help educators and stakeholders assess the extent to which program objectives have been achieved. Several indicators discussed in this study include academic achievement, quality of the learning process, student learning outcomes, learning environment, and evaluation of the learning process itself. Academic achievement is measured through various assessment methods. At the same time, the quality of the learning process includes not only the interaction between teachers and students but also the teaching methods applied. In addition, internal and external factors, including the social and family environment, also affect student learning outcomes. A supportive learning environment is an essential component that can increase student motivation and learning outcomes. This study confirms that evaluation is a crucial component in education because it allows for the assessment of the effectiveness of the teaching strategies and methods used. Educational organizations can conduct regular evaluations to identify the strengths and weaknesses of the program and make necessary improvements to improve learning outcomes. In conclusion, the application of appropriate indicators in educational evaluation is critical in creating an optimal learning environment that is responsive to student needs.